MENUMBUHKAN SEMANGAT PANCASILA SEBAGAI DASAR PERSATUAN DAN KESATUAN BANGSA SEBAGAI UPAYA MELAWAN GERAKAN POPULISME DI INDONESIA - Adon, Mathias Jebaru (Publicio: Jurnal Ilmiah Politik, Kebijakan dan Sosial, 2022)
Populism arose in the midst of an unfavorable economic situation and the failure of moderate politicians to solve the problem. This tension is used by populist leaders and parties to rule and control the opposition. They use religious sentiments and sectarian identities to win popular support. Based on this, the research of this study aims to elaborate on the issue of popoulism in global politics, how religious conservatism develops and the example of Trump's populist leader who shows the close relationship between religious conservatism and populism. The methodology used in this study is literature research with a phenomenological approach to the development of populist politics in relation to religious conservatism both in the global political arena as seen in Trump's political campaign using religious sentiment. The same issue is used when campaigning for regional head elections in Indonesia. Faced with this phenomenon, Indonesia sets its sights on Pancasila as the foundation in building brotherhood and unity. Pancasila was born from the hope that the Indonesian nation could be siblings to one another despite their diversity. Indonesia sets its sights on Pancasila as the foundation for building brotherhood and unity. Pancasila was born from the hope that the Indonesian nation could be siblings to one another despite their diversity. Indonesia sets its sights on Pancasila as the foundation for building brotherhood and unity. Pancasila was born from the hope that the Indonesian nation could be siblings to one another despite their diversity.